Pengaruh Brand Image Dan Promosi Penjualan Terhadap Keputusan Pembelian Kentucky Fried Chicken (KFC) Cabang Sipin Di Kota Jambi (Studi Kasus KFC Sipin) - Melia Widlim (Science of Management and Students Research Journal (SMS), 2022)
This research consist of independent variable that is brand image, promotion  and dependent variable that is purchasing decision. The formulation of the problem how the influence of independent variable to the dependent variable simultanesously and partially. Lifestyle indicators among others : activities, interest and opinion. The indicator of consumers purchasing decisions are product selection, brand choice, distributor choice, time of purchase, purchase amount. Meansuremen of each indicator of lifestyle as well as the consumers purchasing decision to buy the product Kentucky Fried Chicken (KFC) Branch of Jambi City above using descriptive analysis using interval scale.Kentucky Fried Chicken (KFC) was founded by Colonel Harland Sanders is one of the global businesses in the food service industry and is widely known throughout the world as the face of Colonel Sanders. KFC is known especially for its fried chicken.Regression equations y = 5,117 + 1,003 = 6,12, value determinasions (R2) = 0,585 that meanst the amount of contribution the variable lifestyle (X) able to influence variable consumer purchasing decisions (Y) of 58,5% while the remaining 41,5% are influenced by other variables outside this study.